2018
DOI: 10.1002/elsc.201800071
|View full text |Cite
|
Sign up to set email alerts
|

Study of prebiotic potential and antioxidant activity in Plantago spp. leaves after enzymatic hydrolysis with hemicellulase and xylanase

Abstract: The leaves of Plantago species have been known as a rich source of polysaccharides, polyphenols, and iridoids. In the recent years, some authors have examined the relative influence of carbohydrate compositions and polyphenols on their antioxidant and prebiotic activity. In this study enzymatic hydrolysis of Plantago major, Plantago lanceolata, and Plantago media leaves with hemicellulase and xylanase was carried out. The chemical composition of the enzyme‐derived hydrolysis products was determined. Their anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
(35 reference statements)
1
4
0
Order By: Relevance
“…Results showed that PA stimulated the growth of L. rhamnosus better than glucose within 4 to 6 hours of incubation; albeit, growth of the probiotic did not significantly improve thereafter. This result is similar to the findings of Lukova et al (2018), in that, growth in vitro of L. plantarum strains in the culture medium containing 10% hydrolysates from dried leaves of Plantago spp. was significantly lower after 24 hours of incubation, as compared to the medium with glucose.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Results showed that PA stimulated the growth of L. rhamnosus better than glucose within 4 to 6 hours of incubation; albeit, growth of the probiotic did not significantly improve thereafter. This result is similar to the findings of Lukova et al (2018), in that, growth in vitro of L. plantarum strains in the culture medium containing 10% hydrolysates from dried leaves of Plantago spp. was significantly lower after 24 hours of incubation, as compared to the medium with glucose.…”
Section: Discussionsupporting
confidence: 91%
“…was significantly lower after 24 hours of incubation, as compared to the medium with glucose. The poor growth response of the studied lactobacilli was probably due to the presence of galactose and arabinose, which are difficult to metabolize (Lukova et al 2018). In contrast, Chimtong et al (2016) reported that oligosaccharides derived from hydrolysed spent tea leaves improved growth in vitro of L. acidophilus after 18 hours incubation, compared to glucose.…”
Section: Discussionmentioning
confidence: 85%
“…Our previous studies and other publications are envisaged to understand in detail the metabolism of XOSs by Lactobacillus spp. [ 27 , 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained by Grigore et al [ 61 ] in the antioxidant enzyme activity assays suggest a higher antioxidant potential of P. media (compared with other Plantago species), and a superior activity in the flowering phenophase. Lukova et al also obtained superior results in the in vitro antioxidant assays for the hoary plantain, compared with P. major and P. lanceolata , although significantly lower compared with the values obtained for the BTH standard, for ethanol extracts, hemicellulose, respectively xylanase hydrolysates) [ 31 , 62 ].…”
Section: Main Constituents and Applicationsmentioning
confidence: 99%